Effects of salt and rice flour concentration on microbial diversity and the quality of sour meat, a Chinese traditional meat - Mengyang Liu; Xinping Lin; Jing Yang; Xu Yan; Chaofan Ji; Huipeng Liang; Sufang Zhang; Liang Dong (Food Science and Human Wellness)
This study investigated the effects of salt (3% and 6%, m/m) and rice flour (10% and 20%, m/m) addition in sour meat, a traditional Chinese fermented meat. It was found that salt has greater effect than rice flour addition in spontaneous fermentation. Low-salt groups had lower pH and higher titratable total acid. In the low-salt groups, the dominant genera were Lactobacillus and Lactococcus, whereas Staphylococcus, Weissella, and Tetragenococcus were dominant in the high-salt groups. Higher total free amino acids and essential amino acids, organic acids, hexanoic acid ethyl ester and octanoic acid ethyl ester were found in the low-salt groups. The RDA analysis revealed that Lactococcus was closely related to product quality, with the S3F10 (3% salt and 10% rice flour) group outperforming the others in the sensory evaluation. Therefore, 3% salt and 10% rice flour were considered more appropriate for the production of healthy and tasty fermented sour meats.